2016
DOI: 10.13075/ijomeh.1896.00736
|View full text |Cite
|
Sign up to set email alerts
|

Professional activity, information demands, training and updating needs of occupational medicine physicians in Italy: National survey

Abstract: Objectives: Occupational medicine is a discipline continually evolving in response to technological advances, changes in workplaces and production processes, emergence of new occupational risks and diseases and modifications in regulatory framework for occupational health and safety. Therefore, the recurrent revaluation of professional activity, information demands and education and training needs of occupational physicians is essential in order to identify methodologies and tools that may contribute to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…However, it must be considered that according to our survey data, a great number of companies do not make any use of professional OSH consultants, or, if they do, are still quite often dealing with OSH specialists who have little expertise in psychosocial risk prevention and show rather low attention to that issue in their daily practice. The latter is certainly true for safety engineers (Hamacher et al 2013; LeitĂŁo and Greiner 2017), whereas findings for occupational physicians are more mixed (Harber et al 2010; Persechino et al 2016). Overall, the potential benefits of OSH specialist assistance for promoting psychosocial risk assessments still seem far from being fully exploited.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be considered that according to our survey data, a great number of companies do not make any use of professional OSH consultants, or, if they do, are still quite often dealing with OSH specialists who have little expertise in psychosocial risk prevention and show rather low attention to that issue in their daily practice. The latter is certainly true for safety engineers (Hamacher et al 2013; LeitĂŁo and Greiner 2017), whereas findings for occupational physicians are more mixed (Harber et al 2010; Persechino et al 2016). Overall, the potential benefits of OSH specialist assistance for promoting psychosocial risk assessments still seem far from being fully exploited.…”
Section: Discussionmentioning
confidence: 99%
“…Workplaces should be considered in all respects potential obesogenic environments since they can directly affect weight-related behaviors and the lifestyles of workers while at the same time exposing them to occupational risk factors that can have a significant impact on the physiology of the human body [20][21][22][23]. For example, scientific progress and technological innovation have greatly influenced the labor market, leading to increased levels of computerization, automation and mechanization [21,24,25]. These changes have modified the types of task in which workers are involved, reducing strenuous heavy work while increasing sedentary jobs [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The report of Japan Medical Association 22) In 2016, majority of OP felt difficulty in SC-related issues, especially in interview with high-stress employees ( Table 5). In many countries, mental health-related issues are one of the main targets of OH activities 14,27) . In / 23 Japan, a questionnaire survey for OPs belonging to an enterprise or OH service organization (that may mean full-time OP) showed that 86% of OPs felt employers' high expectation for mental health related activities as well 28) .…”
Section: The Results Of Classification By Type Of Business Of Enterprmentioning
confidence: 99%
“…Reports on the activities and job demand of OPs have been published 7 / 7 by several research groups [8][9][10][11][12][13][14][15] as well as by a number of regional occupational health promotion centers [16][17][18] . Nevertheless, there are no currently available reports on the difficulties experienced by private clinicor hospital-based part-time OPs in their daily OHS or that evaluate the time spent by OPs in various OHS activities except for Moriguchi et al 19) .…”
Section: A Nation-wide Survey Conducted By the Ministry Of Health Lamentioning
confidence: 99%